البنيوية الأدبية في جهود كلود بيشوا و اندريه ميشال روسو - عزيزي, رشيدة (كلية الأدب العربي والفنون, 2024)
يعدّ موضوع الأدب المقارن من أبرز الدّراسات الأدبيّة في العصر الحديث، يهتمّ بدراسة ومقارنة الأدبيات من مختلف الثقافات واللغات،كما يسلط الضوء على التشابهات والاختلافات بين الأعمال الأدبيّة في مختلف السياقات الثقافية، كما إنّه يلعب دورا حيويا في تعزيز الأدب الوطني، وربطه بالأدب العالمي من خلال عدّة وسائل كالكتب والرحلات، والحروب، كما تبين في كتاب "الأدب المقارن لكلود بيشوا و أندريه م روسو الذي يعدّ من الكتب المهمّة في الدراسات أنّ الأدب المقارن أعظم علم من العلوم وأكثرها نفعا The subject of comparative literature is one of the most prominent literary studies in the modern era. It is concerned with studying and comparing literature from various cultures and languages. It also highlights the similarities and differences between literary works in various cultural contexts. It also plays a vital role in promoting national literature and linking it to world literature. Through several means, such as books, trips, and wars, as was shown in the book “Comparative Literature by Claude Peshua and André M. Rousseau, which is considered one of the important books in studies, that comparative literature is the greatest and most useful science among the sciences.
Keywords: البنيويّة، الأدبيّة، المقارنة; structuralism, literature, comparison.